ANÁLISE HISTOLÓGICA E MOLECULAR EXTRA INTESTINAL DE CAMUNDONGOS TRATADOS COM NANOPARTÍCULA LIPÍDICA SÓLIDA CONTENDO CURCUMINA E CAPSAICINA EM MODELO DE COLITE ULCERATIVA - Teixeira, Maria Luiza Machado (2023)
Ulcerative colitis has a high incidence and may be related to the development of some types of cancer, making it necessary to study alternative drugs that are not toxic to the patient. However, currently, the amount of drugs available is still limited, and unsatisfactory effects have been reported due to the use of these drugs. Thus, studies seek alternative substances for treatment, such as curcumin, for example, as it has anti-inflammatory properties, inhibiting inflammatory markers and reducing the inflammatory process. Curcumin is one of the most used compounds for the treatment of ulcerative colitis, however, given the above, this compound has low oral bioavailability, therefore, the combination with nanoparticles increases its absorption and solubility. In this study we aimed to analyze possible DNA damage in extra-intestinal tissues of mice treated with nanoparticles containing curcumin and capsaicin. By means of agarose gel electrophoresis, we analyzed double and single strand breaks in mice submitted to treatment with dextran to induce ulcerative colitis and with the nanoparticle for treatment. The results of treatments to evaluate DNA damage showed that treatments with dextran sodium sulfate, sulfasalazine and with the nanoparticle were not able to induce damage at the DNA level, double-stranded in kidney and liver and single-stranded in kidney, liver and spleen. With regard to histological analysis, no changes were found in the tissues, all maintained their tissue architecture intact. Thus, we can conclude that dextran sodium sulfate and sulfasalazine do not cause genotoxicity in tissues, however the treatment with solid lipid nanoparticle containing curcumin and capsaicin showed an increase in the number of double strand breaks in relation to the control in the spleen.